2010
DOI: 10.1002/ajmg.b.31083
|View full text |Cite
|
Sign up to set email alerts
|

Association of ZDHHC8 polymorphisms with smooth pursuit eye movement abnormality

Abstract: The zinc finger DHHC domain-containing protein 8 (ZDHHC8) is located in the 22q11 microdeletion region and may contribute to the behavioral deficit associated with 22q11 deletion syndrome. Although polymorphisms of ZDHHC8 have been reported to be associated with the risk of schizophrenia, those associations are still controversial. This study was performed to validate the genetic association of ZDHHC8 polymorphisms with the risk of schizophrenia, and also to scrutinize the association with smooth pursuit eye m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…In a previous study [Liu et al, 2002], a RANBP1 polymorphism (rs175163) was associated with schizophrenia vulnerability in non-22q11 deleted individuals. Our previous study also showed that ZDHHC8 SNPs, a nearby (4 kb) gene of RANBP1 were associated with SPEM abnormality in Korean schizophrenia patients [Shin et al, 2010]. Based on these previous studies about schizophrenia and SPEM abnormality, it is hypothesized that RANBP1 plays an important role in the development of schizophrenia.…”
Section: Neuropsychiatric Geneticsmentioning
confidence: 86%
See 4 more Smart Citations
“…In a previous study [Liu et al, 2002], a RANBP1 polymorphism (rs175163) was associated with schizophrenia vulnerability in non-22q11 deleted individuals. Our previous study also showed that ZDHHC8 SNPs, a nearby (4 kb) gene of RANBP1 were associated with SPEM abnormality in Korean schizophrenia patients [Shin et al, 2010]. Based on these previous studies about schizophrenia and SPEM abnormality, it is hypothesized that RANBP1 plays an important role in the development of schizophrenia.…”
Section: Neuropsychiatric Geneticsmentioning
confidence: 86%
“…The different ethnicity may be a major factor responsible for the discrepancy between the two study populations. In our previous reports about the association of COMT and ZDHHC8 with SPEM abnormality in schizophrenia patients, only ZDHHC8 polymorphisms showed strong association with SPEM abnormality in schizophrenia group [Park et al, 2009;Shin et al, 2010]. To further understand the genetic effects of the nearby gene upon SPEM abnormality in schizophrenia, we carried out an association analysis between RANBP1 and SPEM abnormality among Korean schizophrenic patients.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations